The impact of culturally responsive materials on student motivation and language learning outcomes - Wulan Desi Safitri; Abdul Halim; Ibrahim Ibrahim (Universitas Pendidikan Indonesia, 2025)
English plays a vital role in education, communication, and career opportunities, particularly in countries like Indonesia, where it is taught as a foreign language (EFL). However, many students struggle with motivation and achieving effective learning outcomes. This study investigates the impact of Culturally Responsive Materials (CRM) on student motivation and English learning outcomes among EFL learners. CRM is designed to reflect students’ cultural backgrounds, making learning more meaningful and engaging. The study addresses the need for inclusive teaching approaches and fills gaps in previous research that focused more on teaching strategies than on materials. Using a quasi-experimental method, 60 students from SMA Negeri 2 Loa Kulu were randomly assigned to either a control or experimental group. The control group used conventional materials, while the experimental group was taught using CRM. Motivation was measured with a customized questionnaire, and learning outcomes were assessed through quizzes. The findings revealed that students taught with CRM showed significantly higher motivation (p = 0.034) and improved learning outcomes (p = 0.005) compared to those in the control group. These results suggest that culturally relevant content not only enhances academic performance but also fosters emotional engagement and motivation in EFL contexts. Abstrak Bahasa Inggris memiliki peran penting dalam pendidikan, komunikasi, dan karier, terutama di Indonesia di mana bahasa ini diajarkan sebagai bahasa asing (EFL). Namun, banyak siswa yang mengalami kesulitan dalam menjaga motivasi dan meraih hasil belajar yang optimal. Penelitian ini mengkaji pengaruh Materi Responsif Budaya (CRM) terhadap motivasi belajar dan hasil belajar bahasa Inggris pada siswa EFL. CRM dirancang untuk mencerminkan latar belakang budaya siswa, sehingga pembelajaran menjadi lebih relevan dan menarik. Penelitian ini menggunakan metode kuasi-eksperimental dengan melibatkan 60 siswa dari SMA Negeri 2 Loa Kulu yang dibagi menjadi kelompok kontrol dan eksperimen. Kelompok kontrol menggunakan materi konvensional, sedangkan kelompok eksperimen diajarkan dengan CRM. Motivasi diukur menggunakan kuesioner, dan hasil belajar dievaluasi melalui kuis. Hasil penelitian menunjukkan bahwa siswa yang diajar dengan CRM memiliki motivasi belajar yang lebih tinggi (p = 0,034) dan hasil belajar yang lebih baik (p = 0,005) dibandingkan kelompok kontrol. Temuan ini menunjukkan bahwa materi yang relevan secara budaya tidak hanya meningkatkan kinerja akademik, tetapi juga mendorong keterlibatan emosional dan motivasi siswa dalam pembelajaran bahasa Inggris. Kata Kunci: EFL; hasil belajar; motivasi; pendidikan inklusif; pengajaran responsif budaya